2015
DOI: 10.1007/s00441-015-2300-y
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling in bone marrow niche

Abstract: The bone marrow (BM) niche is a specific physiological environment for hematopoietic and non-hematopoietic stem cells (HSCs). Several signaling pathways (including Wnt/β-catenin) regulate various aspects of stem cell growth, function and death in the BM niche. In addition, the canonical Wnt pathway is crucial for directing self-renewal and differentiation as important mechanisms in many types of stem cells. We review the role of the Wnt/β-catenin pathway in the BM niche and its importance in stem cells. Releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 145 publications
4
34
0
4
Order By: Relevance
“…Wnt/β-catenin signaling is an essential pathway in the osteogenic differentiation of MSCs1415. Wnt signaling results in cellular accumulation of Wnt/β-catenin, followed by nuclear translocation of β-catenin and activation of target genes31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt/β-catenin signaling is an essential pathway in the osteogenic differentiation of MSCs1415. Wnt signaling results in cellular accumulation of Wnt/β-catenin, followed by nuclear translocation of β-catenin and activation of target genes31.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling is a crucial regulator of MSCs13 and plays an essential role in osteogenic differentiation1415. Disruption of β-catenin leads to extensive bone marrow adiposity and low bone mass16.…”
mentioning
confidence: 99%
“…As we know, osteoblasts are derived from mesenchymal stem cells (MSCs). Wnt canonical signaling plays an important role in osteoblast differentiation both during embryogenesis and in adult life (50). However, there are several novel members in the LDLR family such as, LRP3, LRP10 and LRP12 (25,29,40), which are uncertain if they are receptors for apoE.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the canonical Wnt/β-catenin signaling pathway are integral for normal osteoblast differentiation as well as the differentiation of several types of stem cells. 32 Fahiminiya et al 33 have reported WNT1 mutations in four children from three families. These children had short stature, low bone density, and multiple vertebral compression fractures in addition to multiple long-bone fractures during the first years of life.…”
mentioning
confidence: 99%